Foreign Language Anxiety (FLA) Progression of Non-English Major University Students in English Classroom - Muhammad Muqoffa; Robiatul Adawiyah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
The objective of this study is to investigate the prevalence and progression dynamics of Foreign Language Anxiety (FLA) among non-English major university students by comparing first-semester (S1, novice) and third-semester (S3, intermediate) learners in the Faculty of Administrative Sciences, Universitas Lumajang. This investigation is theoretically grounded in Horwitz, Horwitz, & Cope’s (1986) seminal conceptualization of FLA as a distinct, situation-specific construct. A quantitative, cross-sectional survey design was employed that involved 40 university students, consisting of 20 S1 students and 20 S3 students. The primary instrument was the 33-item Foreign Language Classroom Anxiety Scale (FLCAS), which was adapted and translated into Bahasa Indonesia. Data analysis utilized descriptive statistics and an Independent Samples T-Test for inter-group comparison. Descriptive results indicated an overall moderate-to-high level of FLA among the participants. Comparative analysis revealed a statistically significant reduction in overall FLA scores for S3 students compared to S1 students. Further analysis of the FLCAS components demonstrated that this overall reduction was overwhelmingly concentrated within the Fear of Negative Evaluation (FNE) sub-component. In contrast, Communication Apprehension (CA) and Test Anxiety (TA) showed no significant reduction and remained persistent affective barriers across both groups. The findings suggest that while exposure and adaptation partially mitigate the fear of judgment (FNE), the inherent pressures of oral performance and high-stakes assessment (CA, TA) persist in the English class.